Determinants of healing among patients with coronavirus disease 2019: the results of the SARS-RAS study of the Italian Society of Hypertension. Issue 2 (February 2021) - Mancusi, Costantino; Grassi, Guido; Borghi, Claudio; Carugo, Stefano; Fallo, Francesco; Ferri, Claudio; Giannattasio, Cristina; Grassi, Davide; Letizia, Claudio; Minuz, Pietro; Muiesan, Maria Lorenza; Perlini, Stefano; et al.
Abstract : Objective: The burst of COVID-19 epidemics in Italy prompted the Italian Society of Hypertension to start an observational study to explore the characteristics of the hospitalized victims of the disease. The current analysis aimed to investigate the predictors of healing among Italian COVID-19 patients. We also assessed the effect of angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers on the outcome. Methods: We designed a cross-sectional, observational, multicenter, nationwide survey in Italy to explore the demographic and clinical characteristics of patients with confirmed COVID-19 infection. We analyzed information from 2446 charts of Italian patients admitted for certified COVID-19 in 27 hospitals. Healing from COVID-19 infection, defined as two consecutive negative swabs, was reported in 544 patients (22.2%), 95% of them were hospitalized. Results: Age and Charlson Comorbidity Index were significantly lower in healing compared with nonhealing patients (63 ± 15 vs. 69 ± 15 and 2 ± 2 vs. 3 ± 2, both P  < 0.05). In multivariable regression model, predictors of healing were younger age (OR: 0.99; 95% CI 0.98–0.99, P  = 0.0001), absence of chronic kidney disease (OR: 0.35; 95% CI 0.17–0.70, P  = 0.003) or heart failure (OR: 0.44; 95% CI, 0.28–0.70, P  = 0.001). In the subgroup of patients suffering from hypertension and/or heart failure ( n  = 1498), no differences were observed in the use of ACE inhibitors and angiotensin receptor blockers. Conclusion: Our study demonstrated that younger age and absence of comorbidities play a major role in determining healing in patients with COVID-19. No effects of ACE inhibitors and angiotensin receptor blockers on the outcome was reported.